2008
DOI: 10.1182/blood-2008-06-162404
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1/fractalkine is released from apoptotic lymphocytes to stimulate macrophage chemotaxis

Abstract: Cells undergoing apoptosis are efficiently located and engulfed by phagocytes. The mechanisms by which macrophages, the professional scavenging phagocytes of apoptotic cells, are attracted to sites of apoptosis are poorly defined. Here we show that CX3CL1/fractalkine, a chemokine and intercellular adhesion molecule, is released rapidly from apoptotic lymphocytes, via caspase-and Bcl-2-regulated mechanisms, to attract macrophages. Effective chemotaxis of macrophages to apoptotic lymphocytes is dependent on macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
351
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 402 publications
(358 citation statements)
references
References 49 publications
4
351
0
3
Order By: Relevance
“…The deficiency of CX3CR1 has also been associated with decreased numbers of macrophages in B-cell germinal centers. 36 Although macrophage recruitment was affected, there was no increase in apoptotic B cells, indicating that the reduced number of macrophages was still capable of efficient clearance. This suggests that several find-me signals may be released by one cell and loss of one may be compensated sufficiently enough by others.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 3 more Smart Citations
“…The deficiency of CX3CR1 has also been associated with decreased numbers of macrophages in B-cell germinal centers. 36 Although macrophage recruitment was affected, there was no increase in apoptotic B cells, indicating that the reduced number of macrophages was still capable of efficient clearance. This suggests that several find-me signals may be released by one cell and loss of one may be compensated sufficiently enough by others.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…It has been observed that apoptotic cells can undergo membrane blebbing and release small vesicles during the death process. Truman et al 36 showed that these blebs can participate in monocyte chemotaxis toward apoptotic germinal center B cells. 35 Later, it was shown that Fractalkine/CX3CL1 (FKN) associated with apoptotic microparticles was a chemotactic factor.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…Dying cells release signals such as ATP, uridine triphosphate, and CX 3 CL1. CX 3 CR1-expressing mononuclear phagocytes migrate toward the dying neurons that release CX 3 CL1 [143][144][145]. M2 macrophages that highly express CX 3 CR1 are considered to be a major subset that engages in phagocytosis as shown in in vitro neuronmicroglia co-culture and organotypic slice culture [146,147].…”
Section: Inflammation Versus Resolutionmentioning
confidence: 99%